2023
DOI: 10.3390/nu15030624
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Health Impact of Multicomponent Exercise and Sustainable Healthy Diet Interventions in the Elderly (MED-E): Study Protocol

Abstract: Data concerning the combined effect of diet and exercise interventions on overall health in the elderly are scarce. The MED-E project’s primary aim is to assess the effect of the different 3-month sustainable healthy diet (SHD) and multicomponent training (MT) interventions on several health outcomes in the elderly. A quasi-experimental study assigned older adults into four groups: (1) SHD, (2) MT, (3) SHD + MT, or (4) control group (CG). The SHD intervention included a weekly offer of a mixed food supply and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…A 2018 study evaluated the quality of life of 407 elderly individuals, as well as their nutritional status and dietary parameters. This study indicated that elderly individuals who did not have good nutritional status, had no appetite or had a dietary pattern outside of their energy needs, reported lower quality of life determinants compared to elderly individuals who had an interest in a dietary pattern according to their needs 24 . Our study is consistent with these results, where it can be observed that the combined and nutrition groups presented signi cant results compared to the combined group, which did not receive nutritional guidance.…”
Section: Discussionmentioning
confidence: 79%
“…A 2018 study evaluated the quality of life of 407 elderly individuals, as well as their nutritional status and dietary parameters. This study indicated that elderly individuals who did not have good nutritional status, had no appetite or had a dietary pattern outside of their energy needs, reported lower quality of life determinants compared to elderly individuals who had an interest in a dietary pattern according to their needs 24 . Our study is consistent with these results, where it can be observed that the combined and nutrition groups presented signi cant results compared to the combined group, which did not receive nutritional guidance.…”
Section: Discussionmentioning
confidence: 79%